Comprehensive Triblock Copolymer Analysis by Coupled Thermal Field‐Flow Fractionation‐NMR. Issue 13 (31st May 2013) - van Aswegen, Werner; Hiller, Wolf; Hehn, Mathias; Pasch, Harald
Abstract: Thermal field‐flow fractionation (ThFFF) is used as a novel fractionation technique to investigate the molecular heterogeneity of PB‐b‐PVP‐b‐P t BMA triblock copolymers. Such copolymers cause major problems in liquid chromatography due to very strong polar interactions with the stationary phase. ThFFF separates the copolymers with regard to size and/or chemical composition based on the normal and thermal diffusion coefficients. The separation mechanism in ThFFF and the chemical composition of the separated species is elucidated by online 1 H NMR. Based on the compositional analysis and a calibration of the system with the respective homopolymers, the samples are quantified regarding their molar masses, chemical compositions, and microstructures providing comprehensive information on the complex structure of these block copolymers. Abstract : For the first time, online coupled field‐flow fractionation 1 H‐NMR is used for the analysis of the molecular structure of triblock copolymers of polybutadiene, poly(2‐vinylpyridine) and poly( t ‐butyl methacrylate). Based on the compositional analysis and a suitable calibration of the system, the samples are quantified regarding molar mass, chemical composition, and microstructure providing comprehensive information on the complex structure of these block copolymers.